Affording or constraining epistemological access: An analysis of a case-based approach in a first year process and materials engineering course. - Kotta, Linda Thokozile (My University, 2006)
The focus of this study was a case-based approach used in the first year course Introduction to Process and Materials Engineering, PRME1002, at the University of the Witwatersrand in 2005. This approach attempted to promote epistemic access to Process and Materials Engineering by moving away from the more traditional decontextualised and contrived engineering problems and introducing context-rich cases entailing more authentic engineering problems. The study investigated the extent to which the context rich problem-solving environment afforded the students epistemic access to Process and Materials Engineering. This was done through an analysis of the form and content of students’ knowledge and problem-solving skills as evidenced in their written responses to case-based problems. A modified form of the Structure of Learning Outcomes (SOLO) taxonomy was used as the instrument of analysis. The research showed that students tended to work in fragmented ways despite the context. They tended not to fully explore the context and as such could not successfully identify the salient aspects. They frequently ignored evidence in the context and invented their own in order to be able to use strategies that they were most familiar with. These findings suggest that that while the case-based approach introduced in the course, theoretically has the hallmarks of an ideal approach with which to create a favourable environment for learning, if students treat knowledge as fragmented and aren’t persuaded by the context to change their ways of working, the case-based approach does not afford students optimal epistemological access.
Faculty of Humanities School of Education 0215438v lkotta@chemistry.uct.ac.za
Keywords: Engineering; Education; Authentic tasks; Solo taxonomy; Problem based learning